Assessment of Reasons for Partial Compliance and Non-compliance to the Routine Childhood Vaccination Schedule in Al-Karkh District - HASSAN, ALI (Iraqi National Journal of Nursing Specialties, 2022)
Abstract Objective (s): To evaluate reasons for partial compliance and non-compliance to the routine childhood vaccination schedule in Al-Karkh district Methodology: Descriptive study , using the evaluation approach, is carried throughout the present study to determine the reasons for the Routine Childhood Vaccination at health care sectors and primary health care centers at Al-Karkh District in Baghdad City, Convenient, non-probability, sample of (90) mother who are recruited from health care sectors at Al-Karkh District in Baghdad City. All mothers, who have participated in the study, have signed consent form for their agreements for the participation in the study. An interview-schedule is constructed for the purpose of the study. The study instrument is constructed through review of relevant literature. It is comprised of reasons responsible for partial compliance and Reasons for Non-compliance to the routine childhood vaccination schedule. Content validity and internal consistency reliability of the study instrument are determined through pilot study. Data are collected through the use of the study instrument and the application of the structured interview as means of data collection. Data are analyzed through the application of the descriptive data analysis approach of frequency, percent and mean of scores. Results: The study depicts that mothers present different reasons for partial compliance and non-compliance for routine childhood vaccination schedule. Conclusion: Reasons for partial compliance for routine childhood vaccination schedule include that the child is ill and family problem including illness of mother, fear of side effects, and the vaccination is postponed until another time in Al-Karkh Districts. These reasons are identified as part of the obstacles, lack of information and lack of motivation reasons and reasons for non-compliance for routine childhood vaccination schedule include that the child is unvaccinated because of illness, fear of side effects after vaccination and the time for vaccination is not convenient in Al-Karkh Districts in Baghdad City. These reasons are discovered as the main causes of the vaccination delay. Recommendations: The study recommends that routine childhood vaccination schedule should be seriously implemented and monitored. Further national studies can be conducted on such topic and on a wide-range scale. Key Words: Partial compliance, Non-compliance, Routine Childhood Vaccination Schedule